Practices at the Boundaries of Business Ethics & Corporate Social Responsibility - Angeli Elizabeth Weller (Copenhagen Business School (CBS), 2016)
In this dissertation, I explore the practices created to manage business ethics and corporate social responsibility in multinational corporations and the relationship between them across three separate but interrelated articles. The first article suggests that these practices are resident in distinct communities of practice, and therefore there are boundaries in both meaning and identity that make alignment between them problematic. The second article looks at the boundaries between these communities by exploring the history of the professional associations in the business ethics and corporate social responsibility field in the United States, as well as their current articulations of knowledge and competence in their respective fields. The third article is a single case study of a company that purposefully aligned ethics, compliance, corporate social responsibility and sustainability practices and managers, and it explores both the enablers of alignment and the learning stages that transformed them into a single community of practice. Theoretically, this work applies communities of practice, an organizational learning theory, within the business and society field, thereby contributing a helpful lens through which to explore responsible business practices and the practitioners that create and implement them. Leveraging this perspective, this research offers a theoretical explanation about why practices are not currently aligned and illuminates both the barriers and enablers to future alignment. Practically, this work shows that boundaries exist between business ethics and corporate social responsibility practices, and calls on scholars and managers who seek alignment to both build intentional bridges between these communities and consider alternate trajectories for the evolution of these practices. Done well, learning across the boundaries between these communities of practice could in turn catalyze managers' understanding of ethics and responsibility in business.
hdl:10398/9352
Keywords: 650